RUMAH SAKIT UMUM KELAS C DENGAN KEUNGGULAN KESEHATAN PARU DENGAN PENDEKATAN HEALING ENVIRONTMENT DI KECAMATAN TUGU, KOTA SEMARANG - Untoro, Fatimah (Jurnal Poster Pirata Syandana, 2024)
Health is one of the most fundamental aspects of human life. Hospitals as one of the building facilities that provide health services should be easily accessible to the wider community, as stated in Article 25 of the Universal Declaration of Human Rights, that every person has the right to a standard of living adequate for the well-being and health of himself and his family. Nevertheless, the number of hospital units in Tugu District, Semarang City, according to the Semarang City Central Statistics Agency as of 2020–2022 is 0 units. Meanwhile, the increase in population in Tugu District, Semarang City in 3 years reached 0.39%. The total population in Tugu District as of 2022 is 33,079 people. If you use the bed to population ratio recommended by WHO of 1:200, the need for hospital beds in Tugu District, Semarang City is 165. Not only that, the complexity of health in Semarang City, in the top 20 morbidities or diseases reported at health centers in Semarang City, 3 of them are diseases that attack the respiratory system. On the other hand, hospitals are often associated with scary buildings that bring sadness. In fact, according to Lidayanana in Khairullah (2022), stress can reduce the human body's immunity which can hamper the healing process. So, a hospital environment is needed that supports patient healing with a design that uses a healing environment approach. According to Jones (2008) as quoted by Berutu, et.al (2023), medical factors only play a role in 10% of the healing process. 20% is played by genetic factors, 30% by other factors, and the biggest factor that plays a role in a person's healing or recovery is environmental factors with a role of 40%.